Roles for fibrinogen, immunoglobulin and complement in platelet activation promoted by Staphylococcus aureus clumping factor A. - FOSTER, TIMOTHY (My University, 2005)
Staphylococcus aureus is an important cause of infective endocarditis (IE) in patients without a history of prior heart valve damage. The ability to stimulate the activation of resting platelets and their subsequent aggregation is regarded as an important virulence factor of bacteria that cause IE. Clumping factor A is the dominant surface protein responsible for platelet activation by S. aureus cells in the stationary phase of growth. This study used Lactococcus lactis as a surrogate host to study the mechanism of ClfA-promoted platelet activation. Expression of ClfA from a nisin-inducible promoter demonstrated that a minimum level of surface-expressed ClfA was required. Using platelets that were purified from plasma, the requirement for both bound fibrinogen and immunoglobulin was demonstrated. The immunoglobulin G (IgG) requirement is consistent with the potent inhibition of platelet activation by a monoclonal antibody specific for the platelet FcgammaRIIa receptor. Furthermore the IgG must contain antibodies specific for the ClfA A domain. A model is proposed whereby bacterial cells armed with a sufficient number of surface-bound fibrinogen molecules can engage resting platelet glycoprotein GPIIb/IIIa, aided by bound IgG molecules, which encourages the clustering of FcgammaRIIa receptors. This can trigger activation of signal transduction leading to activation of GPIIb/IIIa and aggregation of platelets. In addition, analysis of a mutant of ClfA totally lacking the ability to bind fibrinogen revealed a second, although less efficient, mechanism of platelet activation. The fibrinogen-independent pathway required IgG and complement deposition to trigger platelet aggregation.